Mapping the intellectual structure of mobile gaming in education: insights from bibliometric methods - Pek, Lim Seong; Mee, Rita Wong Mee; Yob, Fatin Syamilah Che; Wider, Walton; Toquero, Cathy Mae; Talidong, Karen Joy Brillo (International Journal of Evaluation and Research in Education (IJERE), 2025)
Mobile gaming in education encompasses using games on mobile devices to achieve educational goals, offering an interactive platform that can make learning more engaging and accessible. This study addresses the gap in understanding how mobile gaming can enhance educational outcomes by mapping the intellectual landscape of mobile gaming research in education through bibliometric methods. The problem is the growing need to adapt educational tools to students’ digital preferences, balancing engagement with academic rigor. A total of 247 articles were identified from the Web of Science (WoS) database. Through co-citation and co-occurrence analyses, the study identifies influential research themes and emerging trends, such as gamification, serious games, and augmented reality. The findings demonstrate that mobile gaming fosters engagement in promoting motivation and supporting problem-solving skills in educational contexts. However, it also highlights the importance of aligning mobile gaming with curriculum objectives and ensuring instructor readiness, supporting sustainable development goal 4: quality education, which aims to improve inclusive and equitable learning outcomes. It identifies emerging trends, including serious games, technology acceptance models, and the use of augmented reality in educational settings. This study provides a significant impact for educators and researchers seeking to incorporate mobile gaming into educational settings actively. The study suggests a balanced approach to mobile gaming, ensuring its introduction enhances educational goals while minimizing the potential for distraction, fostering innovation in line with sustainable development goal 9: industry, innovation, and infrastructure.